Guidelines for the diagnosis and antimicrobial therapy of canine superficial bacterial folliculitis (Antimicrobial Guidelines Working Group of the International Society for Companion Animal Infectious Diseases). Issue 3 (11th April 2014) - Hillier, Andrew; Lloyd, David H.; Weese, J. Scott; Blondeau, Joseph M.; Boothe, Dawn; Breitschwerdt, Edward; Guardabassi, Luca; Papich, Mark G.; Rankin, Shelley; Turnidge, John D.; Sykes, Jane E.
<x xml:space="preserve">Abstract</x> Background Superficial bacterial folliculitis (SBF) is usually caused by Staphylococcus pseudintermedius and routinely treated with systemic antimicrobial agents. Infection is a consequence of reduced immunity associated with alterations of the skin barrier and underlying diseases that may be difficult to diagnose and resolve; thus, SBF is frequently recurrent and repeated treatment is necessary. The emergence of multiresistant bacteria, particularly meticillin‐resistant S. pseudintermedius (MRSP), has focused attention on the need for optimal management of SBF. Objectives Provision of an internationally available resource guiding practitioners in the diagnosis, treatment and prevention of SBF. Development of the guidelines The guidelines were developed by the Antimicrobial Guidelines Working Group of the International Society for Companion Animal Infectious Diseases, with consultation and advice from diplomates of the American and European Colleges of Veterinary Dermatology. They describe optimal methods for the diagnosis and management of SBF, including isolation of the causative organism, antimicrobial susceptibility testing, selection of antimicrobial drugs, therapeutic protocols and advice on infection control. Guidance is given for topical and systemic modalities, including approaches suitable for MRSP. Systemic drugs are classified in three tiers. Tier one drugs are used when diagnosis is clear cut and risk factors for antimicrobial drug resistance are not present. Otherwise, tier two drugs are used and antimicrobial susceptibility tests are mandatory. Tier three includes drugs reserved for highly resistant infections; their use is strongly discouraged and, when necessary, they should be used in consultation with specialists. Conclusions and clinical importance Optimal management of SBF will improve antimicrobial use and reduce selection of MRSP and other multidrug‐resistant bacteria affecting animal and human health.